32 Does faecal calprotectin measurement have an impact on patient management?. (5th April 2017) - Callaghan, B; Lynch, P; Jacob, S; Caneborg, K; Love, K
Abstract : Background: Faecal calprotectin (FC) is recommended to support the differential diagnosis of IBD or IBS in adults with recent onset lower gastrointestinal symptoms. FC can assess IBD activity in those with known disease, as a rising level is an early marker of potential relapse. There is presently no formal funding for FC within Northern Ireland. Aim: To assess if FC measurement directs an immediate modification in patient management within two out-patient groups: 1) new patients with differential diagnosis of IBS or IBD; 2) review patients with known IBD. Method: A random selection of FC results from secondary care patients over 12 months were analysed. Patient outcomes following the FC result stratified patients into one of four groups: Discharged, colonoscopy performed, clinic review or escalation of medical therapy. Results: Group 1 (n=28): 8 positive FC, all proceeding to endoscopy. In the 14 negative FC, 12 patients were discharged, 2 had clinic review. For indeterminate result: one patient with 2 indeterminate results underwent colonoscopy; 4 had clinic review; 1 was discharged. Group 2 (n=28): of the 20 positive results, 11/20 (55%) had medical management escalated, 5/20 (25%) underwent colonoscopy and 20% had clinic review. In the negative and indeterminate results: 7/8 had clinic review. Conclusions: For patients with suspected IBS, a negative FC avoided unnecessary colonoscopy. In patients with known IBD, a raised FC led to an escalation in therapy in the majority of patients to minimise the risk of relapse and potential hospital admission. This study supports the need for a Northern Ireland FC service.